The unspeakable, the unnarratable, and the repudiation of epiphany in 'Recitatif': a collaboration between linguistic and literary feminist narratologies. Issue 6 (3rd July 2018) - Warhol, Robyn; Shuman, Amy
ABSTRACT: The authors bring together feminist-narratological methodologies from literary studies and linguistic anthropology in a reading of Toni Morrison's short story, 'Recitatif'. Both authors self-identify as 'feminist narratologists', but their two fields seldom interact. They ask what insights their combined approaches bring to interpreting this radically ambiguous fictional text that distinguishes two characters as being 'black' and 'white' without establishing which is which. Instead, race and class are discursively constructed out of perceived difference and affiliation. Pursuing the linguistic discourse analyst's interest in 'the unspeakable' and the literary critic's formulation of 'the unnarratable', rather than ask 'Who is speaking?' the authors consider who cannot or will not speak, especially Maggie, the disabled character whom the narrator assumes is incapable of speech. Morrison's story substitutes shame for the sympathy that readers might ordinarily experience in reading progressive narratives about otherness. Instead of ending on a 'relatable' epiphany, 'Recitatif' presents two protagonists ashamed of their failure to read disability (or even to have understood that disability is neither self-evident nor transparent), just as the story's readers are shamed for their assumption that race shouldn't need to be read, because – as the narrator's silences imply – it supposedly goes without saying.